Mechanochemical modification of crosslinked low‐density polyethylene: Effect of solid‐state shear pulverization on crosslinks, branches, and chain lengths. (20th June 2022) - Zack, Spencer J.; Herrold, Nathan T.; Wakabayashi, Katsuyuki
Abstract: Crosslinked low‐density polyethylene (XLLDPE) is widely used in several specialty plastics industries. However, the permanent chemical crosslinks cause high‐melt viscosity and poor processability, preventing the material from being reused and recycled effectively. This study investigates solid‐state shear pulverization (SSSP) as a continuous, commercially viable mechanochemical processing technique to initiate the decrosslinking of XLLDPE for mechanical recycling. Post‐industrial XLLDPE scrap material was processed using SSSP with a range of pulverization conditions, which were correlated with universal processing covariants of specific mechanical energy and particle size distribution. The physical properties of SSSP‐processed materials were compared to as‐received XLLDPE and uncrosslinked low‐density polyethylene. While gel content tests confirm a gradual decrease in crosslinking density with a more energy‐intensive SSSP process, melt rheology and dynamic mechanical analysis characterization revealed additional chain architecture modifications such as branching and chain scission. Based on differential scanning calorimetry and thermogravimetric analysis, the SSSP‐processed XLLDPE retained its thermal stability and crystallinity; tensile testing results showed improved stiffness, strength, and toughness. These results indicate that tunable SSSP can transform XLLDPE into a decrosslinked, branched, and melt‐processable recycled polyethylene. Abstract : Solid‐state shear pulverization (SSSP) is a modified twin screw extrusion technique that can process high melt‐viscosity materials in an effective, continuous, and sustainable manner. Mechanical recycling of post‐industrial cross‐linked low‐density polyethylene (XLLDPE) is investigated, where SSSP is tuned to decrosslink the network chains. SSSP processing yielded recycled materials that are melt‐processable via conventional mixing and molding techniques.